TOURISM IN THE BRČKO DISTRICT OF BIH DURING THE PANDEMIC OF COVID 19 - Đurić, Aleksandar; Puška, Adis (ACADEMIC REVIEW, 2022)
Until the outbreak of the COVID 19 pandemic, the Brčko District of BiH recorded the growth of tourist traffic and the continuous development of selective forms of tourism. With the emergence of pandemic circumstances, restrictions on movement and numerous other restrictions when it comes to complementary services, the development of tourism has stopped and met with great temptations. The Brcko District government has adopted a series of measures that have mitigated the negative consequences in the economy that have enabled the services sector to save jobs and slowly announce a slight recovery. The paper analyzed the problems that tourism encountered. Tourist traffic was monitored using statistical analyses. It was also studied how the standards and protocols that are important for the development of tourism during the pandemic were applied. The results showed that it is necessary to develop age-specific determinants that should guide the further development of tourism in the Brčko District of BiH.